Lennie Carroll

2021-01-04

Need to find a variable.

$ax+by=cx+z$

solve for x

solve for x

Leonard Stokes

Skilled2021-01-05Added 98 answers

Step 1

Given:$ax+by=cx+z$

Step 2

Solving$ax+by=cx+z$

substract cx from both side of equation.

$ax-cx+by=0+z$

$(a-c)x+by=z$

substract by from both sides of the equation.

$(a-c)x+0=z-by$

$(a-c)x=z-by$

divide both the side of equation by (a-c)

$(1)x=\frac{z-by}{a-c}$

$x=\frac{z=by}{a-c}$

Step 3

Result:$x=\frac{z-by}{a-c}$

Given:

Step 2

Solving

substract cx from both side of equation.

substract by from both sides of the equation.

divide both the side of equation by (a-c)

Step 3

Result: